Adverse effects of levomepromazine in sheep - Lau, Hugo Didonet; Fan, Luiz Carlos Ribeiro; Fialho, Sérgio Amaro Guimarães; Pippi, Ney Luis; Raiser, Alceu Gaspar (Pesquisa Agropecuaria Brasileira, 2014)
Change of hemogram, cardiopulmonary frequency, rectal temperature and rumen motility was studied prior and post application of levomepromazine in eight sheep divided into two groups of equal number. The first group received intramuscularly (2 mg/kg) and the second intravenously (1 mg/kg). The blood samples and the clinical symptoms were gathered prior. 15, 30 and 60 minutes post the drug application. In all animals a decrease of erythrocyte number (8.57 - 7.32 million/mm3) and haematocrit values (32.37 - 27.12%) was observed. Eosinopenia (708.75 - 452.50 mm3) and neutrophilia (2,337.50 - 3,345.00 mm3) were also observed. The leukocytes and lymphocytes counts remained constant. The cardiac and pulmonary frequency decreased 15 minutes after the drug application (130 - 118 bat./min and 97.60 - 49.87 mov./min.). After this time increase (132- 143 bat./min. and 60.00-68.75 mov./min.) was observed. The rectal temperature and rumem motility rate remained practically constant during the experiment.